The Collected Writings of Franz Liszt: F. Chopin - Hall-Swadley, Janita R.; Pekacz, Jolanta T. (Rowman & Littlefield Publishers, 2011)
Shortly after Chopin's death in 1849, Franz Liszt wrote the first full-length biography of his fellow composer. As one of Chopin's friends, Liszt created a unique biography that allows the reader to experience the world of Chopin through the memories of one of his most adamant supporters. This translation is the starting volume of Janita Hall-Swadley's The Collected Writings of Franz Liszt, the very first production of Liszt's entire literary collection in English. In addition to the English translation of Liszt's Gesammelte Schriften, collected and edited by Lina Ramann and published in Germany in 1880/83, each volume contains a Foreword written by a scholar and expert on Liszt and that volume's topic. New research and perspectives in the field of Liszt studies are presented in the introduction to each book in the series, and the translations themselves are enhanced with annotations in accordance with modern standards of musicological research. In Volume 1, Liszt provides insight into Chopin's early childhood and musical development, the cultural traditions and customs that inspired the polonaises and mazurkas, and the final days and hours of the composer before he died. Liszt also offers the reader a psychological view of the composer that had not been seriously undertaken by anyone prior to Liszt. Although Liszt offered what some scholars regard as perhaps an idealized image of the composer, readers will enjoy the personal anecdotes and memories that only one close to the late composer could have known. Liszt even takes on the sensitive topic of the love affair between Chopin and the great French woman writer George Sand, much to the displeasure of the former's family. The Collected Writings of Franz Liszt: Volume 1: F. Chopin includes a thorough discussion of Liszt as an author and the tainted past that surrounded his writings beginning in the 1930s. The much neglected topic of Liszt’s relationship with his publishers is explored, and the critical questionnaires that Liszt had sent to Chopin’s sister in preparation for writing the biography are included. Finally, a discussion of the professional and personal relationship between Chopin and Liszt is provided, making this volume a valuable addition to the study of both composers.